Effect of post-harvest cultural practices on cotton boll weevil, Anthonomlis grandis Boheman, 1843 populations - Soares, José Jandui; Busoli, Antonio Carlos; Yamamoto, Pedro Takao; Sobrinho, Raimundo Braga (Pesquisa Agropecuaria Brasileira, 1994)
The research was carried out at Jaboticabal, SP, Brazil, in order to verify the effect of cultural harvest practices on cotton boll weevil populations. The experimental design was a complete randomized one with four treatments and four replications. The treatments were as follows: 1) post-harvest cotton field; 2) cotton field with mechanical destruction of stalks in late season; 3) treatment 2 plus harrowing of the soil; 4) treatment 3 plus "trap crop" with sprays of insecticides. Four Hardee traps baited with glandlure pheromones were placed in the treatments. The populations of boll weevils were monitored from April 27th to May 25th, 1991. By the results, it was concluded that the association of "trap crop" plus mechanical destruction of stalks in late season and harrowing presented the smallest number of captured boll weevils. The trap efficiency was influenced by the presence of plants with reproductive structures. Index terms: mechanical clearing
Keywords: mechanical clearing harrowing of soil; "trop crops"; insecticides; pheromones